Buriti (Mauritia flexuosa L.f.) as a territorial marker: sociocultural and economic source of Warao women in Amazon (Terr@ Plural, 2023)
The study seeks to discuss the social, cultural, and economic organization and contact between indigenous Warao women and the buriti palm, from which they derive their sustenance, shelter and the way in which it portrays the mythical relationship with all appropriation to meet needs. Furthermore, buriti is a source of income, through handicrafts, clothing and hammocks, the construction of houses, and a source of food. The analysis of the geographical category will be based on the concept of territoriality, through the territorial markers in the related studies by Almeida Silva (2010). Finally, the study was guided by bibliographical research, with data collected through theses, articles, published in the scientific and academic environment, with a qualitative nature and phenomenological analysis, in order to highlight human events in the midst of migratory manifestations.
Keywords: Migrations; Warao Native People; Representations; Territorialities